DETERMINATION OF BACKPACK MASS LIMIT FOR STUDENTS IN A UNIVERSITY IN ABEOKUTA, SOUTHWESTERN NIGERIA - SALAMI OLASUNKANMI ISMAILA (Alma Mater Publishing House "Vasile Alecsandri" University of Bacau, 2016)
The aim of this study was to use the Froude number to determine the mass of the backpack that a student should carry in tertiary institutions. A model was developed using the Froude number with leg length and power of the students as inputs. It was established that a student in tertiary institutions should carry a backpack with a mass of at most 10 % of the body mass. Similar studies are recommended for primary and secondary schools.